Violence and gender roles: the status of women in the violent world of Salvadoran gangs (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
This article aims to investigate, from a gender perspective, the experience lived by women within the maras from a broader look at their status in Salvadoran society, pointing out how the absence of institutional protection and support towards them can also be an element of weakness in the fight against organized crime.
Keywords: El Salvador, maras, violence, gender, human rights.